MOOC Cyber Sastra Anak IDMOOC.ID untuk Meningkatkan Aksesibilitas dan Kualitas Pembelajaran yang Berkelanjutan - M. Kharis; Dudy Syafruddin; Desti Nur Aini; Sri Prameswari Indriwardhani; Sujinah (BRILIANT: Jurnal Riset dan Konseptual, 2026)
The current study addresses the gap in specialized learning materials for the German Language Education program within the LMS for PPG at Universitas Negeri Malang. By integrating gamification elements, this project aims to transform the LMS into an interactive, engaging learning platform. Utilizing ElevenLabs for audio generation and Wordwall for quiz creation, the course is developed on Moodle, with interactive units focused on reading and listening skills for German levels A2 and B1. The five-unit structure incorporates both reading and listening exercises with interactive quizzes designed to reinforce comprehension and facilitate active learning. As a result, this LMS supports high-quality German language instruction, specifically tailored to PPG students while offering accessibility to German learners globally. The platform signifies an innovation in blended learning, enhancing engagement and learning outcomes through the integration of gamified content and interactive assessment.